A phase 2 study of modified lenalidomide, bortezomib and dexamethasone in transplant‐ineligible multiple myeloma. (8th May 2018) - O'Donnell, Elizabeth K.; Laubach, Jacob P.; Yee, Andrew J.; Chen, Tianqi; Huff, Carol Ann; Basile, Frank G.; Wade, Philip M.; Paba‐Prada, Claudia E.; Ghobrial, Irene M.; Schlossman, Robert L.; Burke, Jill N.; Harrington, Cynthia C.; et al.
Abstract: We sought a regimen that incorporates optimal novel agents and balances efficacy with toxicity in transplant‐ineligible multiple myeloma (MM) patients. Our study evaluated modified lenalidomide‐bortezomib‐dexamethasone (RVD lite) in this population and was administered over a 35‐day cycle. Lenalidomide 15 mg was given orally on days 1–21; bortezomib 1·3 mg/m 2 weekly subcutaneously on days 1, 8, 15 and 22; and dexamethasone 20 mg orally was given on the day of and day after bortezomib for 9 cycles followed by 6 cycles of consolidation with lenalidomide and bortezomib. The primary objective was to evaluate the overall response rate (ORR); secondary objectives included safety, progression‐free survival (PFS) and overall survival (OS). Fifty‐three eligible patients were screened between April 2013 and May 2015; 50 received at least one dose of therapy. Median age at study entry was 73 years (range 65–91). The ORR was 86% and 66% of patients achieved a very good partial response or better. Median PFS was 35·1 months (95% confidence interval 30·9–not reached) and median OS was not reached at a median follow‐up of 30 months. Peripheral neuropathy was reported in 31 (62%) patients with only 1 patient experiencing grade 3 symptoms. RVD lite is a well‐tolerated and highly effective regimen, with robust PFS and OS, in the transplant‐ineligible MM population.